Hydrothermal fluid evolution in the Cuonadong Sn–W–Be polymetallic deposit, southern Tibet: indicated by the in–situ element and boron isotope compositions of tourmaline - Xie, Guozhi; Yan, Haibo; Zhang, Rongqing; Wang, Kun; Zhang, Lipeng (Frontiers in Earth Science, 2023)
The Cuonadong Sn-W-Be polymetallic deposit in the Himalayan leucogranite belt is a representative hydrothermal deposit. The role of fluid exsolution directly from magma and the fluid reaction with surrounding rock for the ore-forming element enrichment are still controversial. Tourmaline is a significant B-bearing mineral in the hydrothermal deposit, and its geochemical and B isotopic signatures can record the source and evolution of the ore-forming fluid. Two types of hydrothermal tourmaline in the hydrothermal quartz vein (Tur-1) and skarn (Tur-2) were conducted in this study. Both the Tur-1 and the Tur-2 have low X-site occupancy and mainly belong to the alkali group. The Tur-1 plots in the schorl field, whereas the Tur-2 is largely Mg-rich dravite. The B isotope analyses of Tur-1 have δ11B values of –13.7 to –13.2‰, whereas Tur-2 has higher δ11B values of −11.1 to −9.3‰. The distinct contact relationship and geochemical compositions suggest that the Tur-1 in the hydrothermal vein was formed from a magmatic-hydrothermal fluid with little influence by surrounding rocks and had genetic relationship with the Cuonadong leucogranite. Whereas, the Tur-2 in the skarn involved more fluid from surrounding rock with high δ11B values and strong metasomatic texture. The higher ore-forming element contents in the Tur-2 than those in the Tur-1 indicate that the reaction between the magmatic exsolution fluid and the surrounding rock is essential for the enrichment and precipitation of ore-forming elements.